2019
DOI: 10.1111/jphp.13113
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase inhibitor, TUPS, attenuates isoproterenol/angiotensin II-induced cardiac hypertrophy through mammalian target of rapamycin-mediated autophagy inhibition

Abstract: Objectives To investigate the potential role and mechanism of TUPS, a soluble epoxide hydrolase inhibitor, in cardiac hypertrophy. Methods Rat and H9C2 cell models of cardiac hypertrophy were induced by isoproterenol and angiotensin II, respectively, followed by TUPS treatment. The expression of hypertrophic markers, ANP and BNP, was determined by quantitative real‐time PCR. The abundance of Beclin‐1, LC3, p‐AMPK and phosphorylated‐mammalian target of rapamycin (p‐mTOR) proteins was analysed by Western blot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, there are conflicting reports on the role of autophagy in Ang II-induced cardiac hypertrophy [ 19 ]. Some studies showed that inhibition of the Ang II-induced autophagy suppressed cardiac hypertrophy [ 20 , 21 ]. In contrast, others showed that activation of Ang II-induced autophagy suppressed cardiac hypertrophy [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports on the role of autophagy in Ang II-induced cardiac hypertrophy [ 19 ]. Some studies showed that inhibition of the Ang II-induced autophagy suppressed cardiac hypertrophy [ 20 , 21 ]. In contrast, others showed that activation of Ang II-induced autophagy suppressed cardiac hypertrophy [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…201,202 For example, TUPS treatment reduced the thickness of the heart wall, downregulated the expression of hypertrophy markers atrial and brain natriuretic peptides, and regulated negative autophagy via activation of mammalian target of rapamycin (mTOR) signaling, allowing prevention of myocardial hypertrophy induced by isoproterenol. 202 These data all suggested the therapeutic potential of sEH in heart failure.…”
Section: Biological Potentials For Seh Inhibitionmentioning
confidence: 92%
“…Moreover, increasing EET levels protected against myocardial infarction and left ventricular dysfunction after ischemic injury in Ephx2 –/– mice . Inhibition of sEH with GSK2188931B and TUPS both protected heart failure. , For example, TUPS treatment reduced the thickness of the heart wall, downregulated the expression of hypertrophy markers atrial and brain natriuretic peptides, and regulated negative autophagy via activation of mammalian target of rapamycin (mTOR) signaling, allowing prevention of myocardial hypertrophy induced by isoproterenol . These data all suggested the therapeutic potential of sEH in heart failure.…”
Section: Biological Potentials For Seh Inhibitionmentioning
confidence: 99%
“…Numerous studies have highlighted the potential benefits of sEH inhibition in the inflammatory response 20 , cardiovascular diseases 21 , non-alcoholic fatty liver 22 and renal disease [23][24][25] . A recent study demonstrated that the sEH inhibitor TUPS mitigated isoproterenol/angiotensin IIinduced cardiac hypertrophy by inhibiting mTOR signaling-mediated autophagy 26 , which indicated that sEH is associated with the regulation of autophagy. Furthermore, previous evidence demonstrated that the stabilization of EpFA by treatment with an sEH inhibitor prevented mitochondrial dysfunction, which subsequently reduced ROS generation and blocked the activation of ER stress in diverse diseases including diabetes, cardiovascular and neurodegenerative diseases 27 .…”
Section: Introductionmentioning
confidence: 99%